2006
DOI: 10.1177/0886260506291658
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of and Factors Associated With Intimate Terrorism and Situational Couple Violence Among a Population-Based Sample of Urban Women in the United States

Abstract: It has been proposed that two distinct forms of intimate partner violence exist: intimate terrorism and situational couple violence. This article describes the distribution of factors that characterize intimate terrorism and situational couple violence, including controlling behaviors, violence escalation, and injury, among a representative sample of 331 physically assaulted women living in 11 North American cities. In addition, respondent, partner, and relationship characteristics associated with each form of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 21 publications
(29 reference statements)
3
73
2
Order By: Relevance
“…The rates of perpetration were higher than what has been observed in some IPV studies from SUD treatment samples (41%-54%; e.g., Chermack et al, 2001;Fals-Stewart et al, 2002), in a prior study of an SUD treatment sample examining NPV (53%; Chermack et al, 2000), in community-based samples (28% -35%) (Ehrensaft et al, 2003;O'Leary and Williams, 2006), and in the CTS-II normative college sample (49% males, 35% females; Straus et al, 1996). Moreover, rates of injury in our study were approximately four times higher than the 13% reported by college students in the CTS-II (Straus et al, 1996) and higher than the 33% found in a sample of women reporting IPV within a 2-year time frame (Frye et al, 2006). In addition to high rates of aggression toward nonpartners, our sample also reported high rates of being the recipient of aggression and being injured by nonpartners: 78% psychological aggression, 56% physical aggression, and 46% injury.…”
Section: Discussioncontrasting
confidence: 45%
“…The rates of perpetration were higher than what has been observed in some IPV studies from SUD treatment samples (41%-54%; e.g., Chermack et al, 2001;Fals-Stewart et al, 2002), in a prior study of an SUD treatment sample examining NPV (53%; Chermack et al, 2000), in community-based samples (28% -35%) (Ehrensaft et al, 2003;O'Leary and Williams, 2006), and in the CTS-II normative college sample (49% males, 35% females; Straus et al, 1996). Moreover, rates of injury in our study were approximately four times higher than the 13% reported by college students in the CTS-II (Straus et al, 1996) and higher than the 33% found in a sample of women reporting IPV within a 2-year time frame (Frye et al, 2006). In addition to high rates of aggression toward nonpartners, our sample also reported high rates of being the recipient of aggression and being injured by nonpartners: 78% psychological aggression, 56% physical aggression, and 46% injury.…”
Section: Discussioncontrasting
confidence: 45%
“…For instance, Johnson in his secondary analysis of the data, defined high control by the presence of three or more control items (Johnson, 2008).Such as approach has been criticized as it considers each control item of an equal weight. It may be that presence of any control item should be identified as control not just three or more items (Frye et al, 2006). It may also be worth exploring if it is the control that should be the focus of research as various forms of IPV are usually an attempt to exert control and to get the victim to confirm (Anderson, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The findings revealed that men and women in the community sample were more likely to use SCV (86% of the cases), when men and women were compared in the clinical samples. Johnson's typology has been supported by some researchers (Ansara & Hindin, 2009, 2011Beck et al, 2013;Frye, Manganello, (Meier, 2015). Further research to test Johnson's typology is recommended (Beck et al, 2013;Gulliver & Fanslow, 2015;Hines & Douglas, 2010).…”
Section: Mutual Violent Control Violencementioning
confidence: 99%
“…PT victims are more likely to use shelters and/or hospitals and tend to be underrepresented in large random surveys (Anderson, 2008;Leone, Johnson, & Cohan, 2007). In addition, victims of PT are more likely to suffer from depression, severe injuries, miss work, and experience posttraumatic stress disorder (PTSD; Anderson, 2008;Frye, Manganello, Campbell, Walton-Moss, & Wilt, 2006;GrahamKevan & Archer, 2003;Johnson, 1995Johnson, , 2006Kelly & Johnson, 2008). Johnson (1995) identified CCV as resulting from a conflict that gets out of hand and leads to minor forms of violence.…”
Section: The Impact Of Coercive Control On Ipvmentioning
confidence: 99%